Stress–Strain Model for Low-Strength Concrete in Uni-Axial Compression - Ahmad, Sohaib; Pilakoutas, Kypros; Khan, Qaiser Uz Zaman; Neocleous, Kyriacos (My University, 2015)
© 2014, King Fahd University of Petroleum and Minerals. One of the most significant problems found in non-engineered reinforced concrete structures is poor quality concrete and can lead to brittle failure modes even for small magnitude earthquakes. The statistics of different post-earthquake surveys indicate that the reinforced concrete building stock in developing countries can have a broad range of low-strength concrete, which can vary between 4 and 20 MPa. The lack of information regarding low-strength concrete mechanical characteristics necessitates a study on low-strength concrete and the development of appropriate stress–strain models to realistically simulate the inelastic behaviour of non-engineered structures. This paper presents the methods adopted to produce low-strength concrete in the laboratory. The stress–strain results obtained from compression tests on cylindrical concrete specimens are presented and new expressions for the modulus of elasticity, peak strain and failure strain are developed, which are used in the development of a stress–strain model for low-strength concrete.
Keywords: Compressive strength; Elastic modulus; Low-strength concrete; Mechanical properties; Non-engineered reinforced concrete structures